Work Culture and Bureaucratic Ethics in Public Administration: An Educational Management Perspective on Human Resource Development - Andi Novita; Lindanur Sipatu; Rosida Adam; Andi Indriani Ibrahim; Wisra (Al-Qalam Institue, 2026)
This study aims to examine work culture and bureaucratic ethics in public sector organizations from an educational management perspective. A qualitative approach was employed using a case study design to gain an in-depth understanding of ethical practices, organizational values, and professional behavior among civil servants. Data were collected through interviews, observations, and document analysis, and analyzed using thematic analysis. The findings indicate that work culture and bureaucratic ethics have been generally implemented effectively, reflected in employees’ awareness of moral values such as professionalism, integrity, responsibility, public courtesy, and neutrality. Nevertheless, several challenges persist, particularly the limited internal supervision and insufficient socialization of the bureaucratic code of ethics. As a result, the implementation of ethical work culture remains inconsistent across organizational units and has not been fully internalized as individual professional behavior, instead relying heavily on hierarchical supervision. The study implies that strengthening educational management practices—such as ethical leadership, continuous professional development, and organizational learning—is essential to internalize work culture and bureaucratic ethics sustainably. These findings contribute to discussions on human resource development and ethical governance in public administration.